2016
DOI: 10.31522/p.24.1(51).5
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Creating Place Identity for Podgorica as Observed Through Historic Urban Planning

Abstract: U stvaranju i održavanju prepoznatljive slike nekoga mjesta veliku ulogu imaju postojeće, a prepoznate prirodne i povijesne vrijednosti unutar područja planiranog za njegov razvoj. Odnos planera prema pravilnoj spoznaji i čuvanju tih vrijednosti može se očitati kroz izrađene i usvojene urbanističke planove. Na primjeru grada Podgorice dan je prikaz načina prepoznavanja i planerski odnos prema tim vrijednostima, od prvih urbanističkih planova pa do danas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…With the annexation of Podgorica to the Principality of Montenegro, the planned development of the city began on the undeveloped areas of the right bank of the river Ribnica. The construction period under the first regulation plan of the Russian engineer Vorman, lasted from 1879 to 1945 [54][55][56][57][58]. This plan was developed on an orthogonal grid of streets, with a rectangular square resting on the main connection of the new part of the city, Nova Varoš (better known as Mirkova Varoš) and Stara Varoš, and the city had functionally good connections with inherited urban tissue.…”
Section: The Case Study Areamentioning
confidence: 99%
“…With the annexation of Podgorica to the Principality of Montenegro, the planned development of the city began on the undeveloped areas of the right bank of the river Ribnica. The construction period under the first regulation plan of the Russian engineer Vorman, lasted from 1879 to 1945 [54][55][56][57][58]. This plan was developed on an orthogonal grid of streets, with a rectangular square resting on the main connection of the new part of the city, Nova Varoš (better known as Mirkova Varoš) and Stara Varoš, and the city had functionally good connections with inherited urban tissue.…”
Section: The Case Study Areamentioning
confidence: 99%
“…It shows how people are living in a particular community [1,2]. The traditional architecture of any region anywhere the world characterizes the simplicity of this architecture and the smart usage of the surrounding environmental materials [3][4][5]. In general, traditional architecture is being demolished and abandoned due to many reasons that affect the world's architectural style [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sociologists examine the importance of place through the terms concept of place and nature of place experience. Unfortunately, architects and planners in their process of "place creation" very often neglect the place experience as an essential element of the planning process [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the late sixties and seventies began studying the relationship between the reality and the idea of the space. 31 First studies have shown that equal to actual space, our space perception can be articulated, evaluated and categorized. 32 Tolman was the first who introduced the idea of cognitive mapping when doing the experiment involving rats and mazes.…”
Section: Introduction Uvodmentioning
confidence: 99%